(untitled) (Andamios, Revista de Investigación Social, 2024)
The purpose of the survey is to account for the trends, levels, and risk factors of criminality in Peru. Data from INEI and the Integrated System of Crime and Citizen Security Statistics (DATACRIM) database were used. Quantitative estimates of criminality trends, risk factors, and levels were estimated through cluster analysis and correlations. The results indicate that the departments of Lima and Lima Metropolitana are in Cluster 1, which indicates a high level of criminality. Therefore, it is possible to infer that departments with high levels of criminality in the past will likely continue to experience high levels in the future.